Retrospective and perspective additional professional education in Russia - Shakarova, Inna S.; Goncharova, Olga P.; Dikanova, Marina V.; Isakova, Tamara G.; Abdulbekov, Magomedrasul Z. (University Pedagogical Journal, 2026)
The article traces the main stages of development of additional professional education, highlights the characteristic features of its organisation in the past, and identifies promising areas for the development of additional professional education. It establishes the fundamental principles on which Russian additional professional education is based, identifies the forms and formats of modern quality assurance in additional professional education, and outlines a range of typical problems arising in the process of implementing its objectives and functions. Prospects for the development of additional professional education are determined, taking into account the latest trends in this area of the Russian educational system.
Keywords: professional education; additional professional education; continuous education; history of professional education; Russian additional professional education